Electroacupuncture for the Prevention of Postoperative Cognitive Dysfunction Among Older Adults Undergoing Hip and Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ou, Liang; Shen, Zhen; Zhang, Tiantian; Chen, Zehua; Zhang, Lin; Xu, Daoqing; Kong, Dezhong; Qi, Qi; Huang, Yanchang; Huang, Weichen; Meng, Yingfu (Frontiers in Medicine, 2022)
Background: Postoperative cognitive dysfunction (POCD) is a common surgical complication in elderly patients undergoing hip and knee replacement. Electroacupuncture (EA) may have protective effect on postoperative cognitive function, but relevant evidence remains uncertain. Objective: To systematically evaluate the evidence of EA for the prevention of POCD after total joint arthroplasty. Methods: PubMed, Embase, CENTRAL, CNKI, Wanfang data, VIP and CBM databases were searched until May 1, 2021. Randomized controlled trials (RCTs) in which patients undergoing hip and knee replacement pretreated with EA for preventing POCD were included. The risk of bias was assessed by the Cochrane Collaboration tool. Meta-analysis was performed using Review Manager 5.4. Results: Eleven RCTs with 949 patients were identified. Meta-analysis showed that compared with controls, EA pretreatment significantly reduced the incidence of POCD at 1, 3, and 7 days, 3 and 6 months after operation. EA was also superior in improving Mini-Mental State Examination (MMSE) scores on the third post-operative day, but not on the first post-operative day. Neuron-specific enolase (NSE) and IL-1β in EA group were significantly lower than that in control group. There was no difference in S-100β between the EA group and control group. Compared to control group, TNF-α levels were not significantly lower in the EA group at post-operative hour 0, while significantly deceased at post-operative hour 24 and 48. Conclusions: Our results suggest that EA pretreatment is an effective adjunctive therapy for reducing the incidence of POCD for patients receiving total joint replacement surgery. Its effect was embodied in improving MMSE scores, and NSE, IL-1β, and TNF-α levels, whereas it had no significant effect on S-100β levels. Meanwhile, benefits of EA for improving POCD need further strengthening and support from more large-scale, high-quality and good-homogeneity RCTs.